Kamus Bahasa Arab sebagai Sumber Belajar (Kajian terhadap Penggunaan Kamus Cetak dan Kamus Digital) - Besse Wahida (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2017)
This paper disscusses about using Arabic dictionary as one of Arabic learning source forms. Dictionary as students source to find information related to Arabic-Indonesian vocabulary or Indonesian-Arabic and giving Arabic vocabulary learning experiences. Arabic dictionary from its type divided into printed dictionary and digital dictionary. There are two ways using Arabic printed dictionary : searching word as alphabetics form of beginning letter of root word with neurology and articulation form of beginning letter of pronunciation. Generally, using printed dictionary through word searching as alphabetics is beginning letter form of root word. Meanwhile,using digital dictionary as articulation is beginning letter of pronunciation. Therefore,using online dictionary and software considered to be easily,effective and efficient without mastering neurology first.